Relationship between Clinical, MRI, and Arthroscopic Findings: A Guide to Correct Diagnosis of Meniscal Tears - Antinolfi, P.; Cristiani, R.; Manfreda, F.; Bruè, S.; Sarakatsianos, V.; Placella, G.; Bartoli, M.; Caraffa, A. (Joints, 2017)
Purpose The aim of this prospective study was to compare and correlate clinical, MRI, and arthroscopic findings in cases of suspected meniscal tears. Using arthroscopic findings as the gold standard, the sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of clinical investigation and MRI were evaluated to determine if is possible, after a careful examination, to bypass MRI and perform directly arthroscopy in suspected cases.Methods A total of 80 patients with a history of knee trauma, preoperative RX, and MRI underwent arthroscopy over an 8-month period at our department. All patients had a clinical examination performed by an experienced knee surgeon. These examiners evaluated and recorded the results of three tests: medial and lateral joint line tenderness test, McMurray's test, and Apley's test. The injury was classified as a meniscal tear if there were at least two positive tests. Finally, using the arthroscopic findings as the gold standard, sensibility, specificity, accuracy, positive and negative predictive values of clinical examination, and MRI were evaluated and compared.Results Clinical examination performed by an experienced knee surgeon reported better sensitivity (91 vs. 85%), specificity (87 vs. 75%), accuracy (90 vs. 82%), positive predictive value (94 vs. 88%), and negative predictive value (81 vs. 71%) than MRI for medial meniscal tears. These parameters showed minimal differences for lateral meniscal tears.Conclusion Clinical examination performed by an experienced knee surgeon provided equal or better results to diagnose meniscal injuries in comparison to MRI. MRI is not necessary to confirm these lesions and should not be used as the primary diagnostic tool.Level of Evidence Level II, prospective study.
Keywords: meniscus; tears; knee; examination; meniscal tears; MRI